2021
DOI: 10.3390/biomedicines9081055
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-1-3p, miR-16-5p and miR-122-5p as Possible Risk Factors of Secondary Cardiovascular Events

Abstract: Ischemic event in one arterial territory increases the risk of a subsequent ischemic event. Circulating microRNAs (miRs) emerge as a potential clinical tool to assess risk of subsequent atherothrombotic events such as cardiovascular death (CVD), myocardial infarction (MI) and ischemic stroke (IS). In this prospective study, we searched for athero-specific miRs related to cardiovascular event risk in patients with symptomatic coronary, carotid lesion, or both territories involvements. The choice of particular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Based on our results, one could speculate that an increased expression of the anti-inflammatory miR-16 in response to acute hypoglycaemia might provide some protection against the harmful effects of subsequent hypoglycaemia as it is negatively correlated with inflammatory biomarkers. It should be noted that upregulation of miR-16 expression was also described in patients with acute myocardial infarction [ 49 ]. It was also found that miR-16 along with miR-15a correlate with adverse events at 12-month follow-up in T2DM patients who have undergone percutaneous intervention to correct critical limb ischemia [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, one could speculate that an increased expression of the anti-inflammatory miR-16 in response to acute hypoglycaemia might provide some protection against the harmful effects of subsequent hypoglycaemia as it is negatively correlated with inflammatory biomarkers. It should be noted that upregulation of miR-16 expression was also described in patients with acute myocardial infarction [ 49 ]. It was also found that miR-16 along with miR-15a correlate with adverse events at 12-month follow-up in T2DM patients who have undergone percutaneous intervention to correct critical limb ischemia [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vegter et al found that several miRNAs, related to PAD, could predict future CV complications in patients with heart failure [ 128 ]. Badacz et al identified miRNA-1-3p, miRNA-16-5p and miRNA-122-5p as possible risk factors for secondary ischemic events in patients with carotid and/or coronary artery disease [ 129 ]. In patients with PAD following femoral artery bypass surgery, plasma levels of miRNA-142, miRNA-223, miRNA-155, and miRNA-92a predicted CV events [ 130 ].…”
Section: Micro Rnas and Padmentioning
confidence: 99%
“…Cerebrovascular diseases can lead to death or long-term disability and is a worldwide health concern. Plasma miR-124-3p levels were found to be elevated in patients with acute ischemic stroke (AIS) ( Badacz et al, 2021 ), and the miR-124-3p level was positively correlated with the poor prognosis of these patients based on the modified Rankin score ( Rainer et al, 2016 ). Higher plasma miR-124-3p levels were suggested to be associated with unfavorable outcomes in patients with AIS undergoing thrombolysis, and miR-124-3p is closely related with the severity of stroke ( He et al, 2019 ).…”
Section: Microrna-124 and Cerebrovascular Diseasesmentioning
confidence: 99%